Tax Expenditure--shedding light on government spending through the tax system : Lessons from developed and transition economies - The World Bank; Brixi, Hana Polackova; Valenduc, Christian; Swift, Zhicheng Li (Washington, DC : World Bank, 2004)
Discusses conceptual and methodological issues relating to tax expenditures, provides a framework for evaluating them, offers case studies on government treatment of tax expenditures from developed and transition economies, and outlines generally applicable policy options. Provides case studies of the treatment of tax expenditures in Australia, Belgium, Canada, China, the Netherlands, Poland, and the United States. Each chapter presents how the nation defines tax expenditures and the corresponding benchmark tax system.
Papers presented at the International Forum on Tax Expenditures, Weifang, China, in Dec. 2002.
Includes bibliographical references and index.
rpm 08/09/2016
Loans
Keywords: Tax expenditures; Government spending policy; Finance -- United States; Tax expenditures -- United States; Taxation -- United States